Fabrication and Structural Properties of Al-N-Co-Fe/Zr Thin Film - Oh, Chang-Sup; Kim, Yong-Ha; Han, Chang-Suk (Asian Journal of Chemistry, 2015)
Al-N-Co-(Zr/Fe/Zr-Fe) films were prepared by using a two-facing target type dc sputtering (TFTS) system. The deposited films were annealed isothermally at 773 K and their magnetic properties and resistivity were investigated. This TFTS method is suitable for preparing Al-N-Co-(Zr/Fe/Zr-Fe) films. The X-ray diffraction profile for Al-N-Co-Zr film shows that it crystallized into the phases of AlN and b-Co, while the profiles for Al-N-Co-Fe and Al-N-Co-Zr-Fe films show that they crystallize into three phases of AlN, b-Co and a-Co. Resistivity shows monotonous increase with increasing annealing time for all kinds of films. The highest resistivity was found for Al-N-Co-Fe-Zr film while lowest was obtained for Al-N-Co-Zr films.